Peningkatan hasil pembelajaran tolak peluru melalui modifikasi peluru serbuk kayu warna - Sofirin, Wahyudi Ujang; Wahyudi, Arief Nur; Utomo, Andy Widhya Bayu (Jurnal Porkes, 2023)
The purpose of the problem in this study is to find whether using color wood powder bullet media can further improve the learning outcomes of bullet repulsion in class V students of SDN Kasreman 2. The goal to be achieved is to further improve the learning outcomes of bullet repulsion in class V students of SDN Kasreman 2 through color wood powder bullet media. The method used in this research is class action research. The number of students in class V is 20 students, consisting of 11 male students and 9 female students. The results of the research on improving the learning outcomes of rejecting bullets through modifying color wood powder bullets that in cycle I there were 11 students who were complete or 55%. While those who have not completed are 9 students or 45%. Whereas in cycle II there were student results with a complete classification of 18 students or 90%, while only 2 students or 10% were not complete. In conclusion, from the results of the research that has been carried out, it is proven that the use of color wood powder bullet modification media can improve the learning outcomes of bullet throwing. This can be seen from the increase in achievement from cycle I to cycle II.